Dibalik Maraknya Penggunaan Software Open Source Berbasis Web di Perpustakaan Perguruan Tinggi di Bali - Suhartika, I Putu; Darmana, Ketut (Sunari Penjor : Journal of Anthropology; Vol 2 No 1 (2018), 2018)
This study focuses on the opinion of developers and users of the system consisting of head of library , librarians, and students about the use of open source software in the Library of Higher Education in Bali. It is hoped that various reasons can be expressed regarding the implementation of the system. This research is a qualitative research using a critical approach.The results showed that 83% of State University Libraries and some private universities in Bali use open source SLiMS software for library management. SLiMS was originally developed to replace the Library software of the Ministry of National Education, but then the software was distributed to the community for free. The use of SLiMS in the library undergoes several stages which are not understood by the initial user of the system. Therefore, the head of the library spent substantial funds for software procurement and staff knowledge improvement. The user's expectation that the software is completely free becomes unrealized. In its development, this software needs to customize, and for that, users interact with program developers. They issue guidelines that users must follow. This interaction creates a continuous relationship between developers and users of the system to form the relationship between knowledge and power. In addition, the practice of hegemony has already occurred in the use of such software. This hegemony process ends when the system user has sufficient ability to handle the system.